GNSS Integrity in The Arctic. Issue 4 (15th December 2016) - Reid, Tyler; Walter, Todd; Blanch, Juan; Enge, Per
Abstract: Growing activity in the Arctic calls for high integrity navigation in this region. This can be achieved using Global Navigation Satellite Systems (GNSS) in conjunction with Satellite Based Augmentation Systems (SBAS) or Advanced Receiver Autonomous Integrity Monitoring (ARAIM). Single frequency GPS‐only SBAS is in service in some regions today and is reliant on ground and space infrastructure. ARAIM will be more autonomous and will rely on the multitude of signals and core constellations coming in the future. Here, we examine both SBAS and ARAIM in the context of aviation and maritime requirements in the Arctic. Results demonstrate that the introduction of multi‐frequency and multi‐constellation to these systems enables navigation safety in the Arctic. SBAS brings aircraft precision approach as well as precise maritime operations such as mapping. ARAIM also supports precision approach in addition to autonomous ice navigation at sea but falls short of precision maritime requirements. Copyright © 2016 Institute of Navigation